Design of the austempering heat treatment of a ductile iron differential case aided by computer simulation - Boccardo, Adrian Dante (2018)
Austempered ductile iron is frequently employed in the fabrication of automobile parts due to its good mechanical properties, and its simplicity and low cost of the manufacturing process. The heat treatment design is an important stage, in which parameters such as temperatures and durations are chosen according to the required microstructure, part dimension, and initial characteristics of ductile iron. A coupled thermo-mechanicalmetallurgical model is employed in this work to facilitate the heat treatment design of a ductile iron differential case. The thermal-mechanical model is solved by using a general-purpose software, and the metallurgical model is implemented into it by means of user-defined subroutines. To perform the austempering heat treatment simulation of the part, experimental results were required to complete some basic parameters of the model. In order to select appropriated values of thermal cycle parameters, the numerical model was employed to analyze the influence of austenitizing temperature, and austempering time and temperature in the microstructure, dimensional change of the part, cooling rate, and minimum required time of the heat treatment to obtain a full ausferritic matrix. A good performance of the computational tool was found by comparison of numerical and experimental results.